Prevalensi dan karakteristik infeksi menular seksual di Klinik Anggrek UPT Ubud II pada bulan Januari - Desember 2016 - Ni Putu Candra Nirmalasari P; Md Swastika Adiguna; Ni Made Dwi Puspawati (Universitas Udayana, 2018)
Sexually Transmitted Infections (STI) is one of the world’s major health problems. Bali, and in particular the town of ubud is a world famous tourist destination and often visited by foreigners. This makes Ubud very vulnerable to the spread of STIs. The purpose of this study was to determine the prevalence and characteristics of STI cases based on age, gender and risk factors at the Anggrek clinic UPT Ubud II from January to December 2016. This research is a descriptive research with secondary data gathered from the medical record. Sample of this research is medical record of STI patient who came to Anggrek clinic UPT Ubud II in the period of 1 January - 31 December 2016 with amount of 273 samples. Secondary data are further processed statistically by using statistical software.The results of the study showed the most frequent STIs were HIV, there were 134 cases (49.1%), followed by Syphilis with 69 cases (25.3%), Gonorrhea with 61 cases (22.3%) and Condyloma Akuminata with 9 cases (3.3%). Men had the higher incidence of STI with 251 cases (91.9%) whereas in women there were only 22 cases (8.1%). The highest STI population was in the age group of 25-49 years where there were 166 cases (60.8%). The highest risk factor for Condyloma acuminata, gonorrhea and syphilis was 79 people (56.8%), in HIV the highest risk factor was homosexual (MSM) of 112 cases (83.6%). It can be concluded that the characteristic of STI patients found is HIV as the most frequent type of STI, where the incidence of STIs is more common in males, in the 25-49 age group with homosexual (MSM) risk factors. Keywords: STI, Ubud, Characteristics